The Relationship between Family Support and Self-Care Behavior among Individuals with Hypertension in Tangerang - Simanullang, Elistina; Simatupang, Jessica Margaretha; Siregar, Septiana Sry Rezeki; Sinulingga, Elysabeth; Sihaloho, Shinta Marina J.P. (Nursing Current: Jurnal Keperawatan, 2025)
Background: Uncontrolled hypertension can lead to severe complication and is a significant contributor to mortality. The family serves as a key functional component in supporting individuals with hypertension, playing a critical role in improving self-care behaviors. Purpose: This study sets out to examine the relationship between family support and self-care behaviors among individuals with hypertension in a community health center in Tangerang Method: A cross-sectional design was employed involving 88 respondents selected through accidental sampling. Data were analyzed using the Pearson chi-square test. Result: The finding revealed that 52 respondents (59.1%) had moderate self-care behavior, and 74 respondents (84.1%) had good family support. The Pearson chi-square test revealed no significant association between family support and self-care behavior (p > 0.05). Conclusion: There was no significant association between family support and self-care behavior among individuals with hypertension. These results suggest that healthcare providers should continue to educate and involve families while also empowering individuals to take an active role in managing their condition. Future intervention study encourages additional strategies alongside family support that effectively promote self-care behaviors.